Le traité de Fort Jackson, 9 août 1814 - Jean‑Marc Serme (Transatlantica)
This paper aims to show the motives and goals of the different actors of the War of 1812 as expressed through the Muscogee Creek War (1813‑1814). The fate of the region was sealed when a gigantic land cession was conceded by Native Americans in the Treaty of Fort Jackson. Aug.9, 1814, symbolizes both the end of Native American clout in the Old Southwest and the beginning of a new era in Southern history. Andrew Jackson played a key‑role in this shift in power. Other individuals, but also social groups and entire nations were involved in a complex web of relationships and cultural, political and economic conflicts.